A comparative study of the nexus between modes of liberation and regime survival: the case of Zambia and Zimbabwe - Munemo, Douglas (Midlands State University, 2016)
Regime change politics has dominated political discourse in Southern Africa in the neoliberal era. It has mainly been characterized by regime change agendas hatched and championed by neo-liberal forces and domestic actors seeking to replace southern African revolutionary nationalist governments with pro-western democratic governments. This paper is a theoretical analysis of the politics of regime change in post-colonial Zambia and Zimbabwe. The paper explores the downfall of the United National Independence Party (UNIP) regime in Zambia and the persistence of the Zimbabwe African National Union Patriotic Front (ZANU PF) regime in Zimbabwe. While acknowledging that a multiplicity of factors influenced regime change politics in both Zambia and Zimbabwe, the study argues that the demise of the UNIP regime and the survival of the ZANU PF regime are rooted in their revolutionary pasts. The former was a pure political movement that achieved independence through political struggle while the latter was a politico- military movement that obtained independence through armed struggle. This diference in identity and mode of attaining independence shaped and influenced the manner in which the movements responded to regime change agendas.